(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the history of periodical publications issued in the districts of the Khorezm region during the Second World War. It analyzes selected articles published in those newspapers. Particular attention is given to the activities and literary contributions of Umar Qurbaniy, as well as a review of articles published in the newspaper Kommunа, which was issued in Khiva.